Employer attitudes, the marginal employer and the ethnic wage gap - Magnus Carlsson; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2011)
Ethnic minorities have lower wages compared to the ethnic majority in most EU-countries. However, to what extent these wage gaps are the result of prejudice toward ethnic minority workers is virtually unknown. This study sets out to examine what role prejudice play in the creation of the ethnic wage gap in one of Europe's most egalitarian countries, Sweden. The analysis takes into account the important distinction between average employer attitudes and the attitude of the marginal employer. Our results confirm that the attitudes of the marginal employer - but not those of the average employer - are important for the ethnic wage gap. This relationship becomes even stronger when potential measurement error and other forms of endogeneity are accounted for by controlling for a rich set of variables and implementing instrumental variable techniques.
urn:nbn:de:101:1-201201114029
Keywords: J64; J71; 330; attitudes; prejudice; marginal employer; ethnic wage gap; Lohndifferenzierung; Ethnische Gruppe; Unternehmer; Arbeitsnachfrage; Meinung; Arbeitsmarktdiskriminierung; Schweden